Effects of meteorological parameters on air pollutant concentrations in Elazig, Turkey - Akpinar, Ebru Kavak; Akpinar, S.; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2006)
In the present study, air pollutant concentrations have been analyzed statistically with meteorological factors in the city of Elazig, which is located in the east Anatolia region of Turkey, for the months of September, October, November, December, January, February, March, and April during the years 2003 and 2004. SPSS code was used for statistical analyses. The relationship between monitored air pollutant concentrations, such as SO2 and the total suspended particles (TSP) data, and meteorological factors such as wind speed, temperature, relative humidity and pressure was investigated. According to the results of linear and non-linear regression analysis, it was found that there is a moderate and weak level of relation between the air pollutant concentrations and the meteorological factors in Elazig. The correlation between the previous day's SO2, TSP concentrations and actual concentrations of these pollutants on that day was investigated and the coefficient of determination R was found to be 0.80 and 0.76, respectively. The statistical models of SO2 and TSP, including all of the meteorological parameters, gave all R of 0.50 and 0.40, respectively. Further, in order to develop this model, the previous day's SO2 and TSP concentrations were added to the equations. The new model for SO2 and TSP was improved considerably with R = 0.85 and 0.80, respectively.
Keywords: sulphur dioxide; total suspended particles (TSP); meteorological parameters; regression analysis; Elazig - Turkey